Learned helplessness and social avoidance in the Wistar-Kyoto rat - Nam, Hyungwoo; Clinton, Sarah M.; Jackson, Nateka L.; Kerman, Ilan A. (Frontiers in Behavioral Neuroscience, 2014)
The Wistar-Kyoto (WKY) rat is an established depression model characterized by elevated anxiety- and depression-like behavior across a variety of tests. Here we further characterized specific behavioral and functional domains relevant to depression that are altered in WKY rats. Moreover, since early-life experience potently shapes emotional behavior, we also determined whether aspects of WKYs' phenotype were modifiable by early-life factors using neonatal handling or maternal separation. We first compared WKYs' behavior to that of Sprague–Dawley (SD), Wistar, and Spontaneously Hypertensive (SHR) rats in: the open field test, elevated plus maze, novelty-suppressed feeding test, a social interaction test, and the forced swim test (FST). WKYs exhibited high baseline immobility in the FST and were the only strain to show increased immobility on FST Day 2 vs. Day 1 (an indicator of learned helplessness). WKYs also showed greater social avoidance, along with enlarged adrenal glands and hearts relative to other strains. We next tested whether neonatal handling or early-life maternal separation stress influenced WKYs' behavior. Neither manipulation affected their anxiety- and depressive-like behaviors, likely due to a strong genetic underpinning of their phenotype. Our findings indicate that WKY rats are a useful model that captures specific functional domains relevant to clinical depression including: psychomotor retardation, behavioral inhibition, learned helplessness, social withdrawal, and physiological dysfunction. WKY rats appear to be resistant to early-life manipulations (i.e., neonatal handling) that are therapeutic in other strains, and may be a useful model for the development of personalized anti-depressant therapies for treatment resistant depression.